ỨNG DỤNG THIẾT BỊ ĐO TỰ ĐỘNG KHẢO SÁT ẢNH HƯỞNG CỦA NƯỚC THẢI TỪ THÀNH PHỒ HỒ CHÍ MINH ĐẾN CHẤT LƯỢNG NƯỚC SÔNG CẦN GIUỘC - Thu Hà, Vũ Thị; Phép, Huỳnh Thị (Vietnam Journal of Science and Technology, 2012)
SUMMARY The impacts of wastewater from Ho Chi Minh city on water quality of Can Giuoc river (Long An) have been investigated using an computerized water quality measurement system developed in Institute of Chemistry, Vietnam Academy of Science and Technology. Main parameters of interests were: dissolved oxygen, pH, total dissolved solids, oxidation - reduction potential etc. The obtained data showed that: through several channels in southern districts of Ho Chi Minh city: Binhchanh, Nhabe waste waters from Ho Chi Minh city with high content of BOD strongly influenced on water quality of Can Giuoc river, namely reduces dissolved oxygen. If this situation goes on, not only aquaculture but also health of inhabitants along this river can be certainly damaged. Keywords. water quality of Can Giuoc river, dissolved oxygen, total dissolved solids.